Isolation of Essential Oils from Essential Roots (Vetiveria zizanoides L.) with Preparation Using Liquid Nitrogen - Arif Ashari; Ciptati Ciptati (Department of Chemistry - Universitas Bangka Belitung, 2019)
Fragrant root oil production can be done by various methods including distillation, pressing, extraction using solvents and extraction using solid fat. Efforts to increase the production of quality fragrant root oil before the extraction process carried out 2 treatments on the sample, namely chopping and preparation using liquid nitrogen. Research that has been carried out sample preparation using N2 (l) has proven to be effective in increasing oil yield. In fresh samples, the yield of oil obtained from the steam-hydro distillation method is 0.84% (variation 1) and 1.2% (variation 2) while for the socletation method is 1% (variation 1) and 2.4% ( variation 2). From the results of GC-MS analysis, the fragrant root oil of the dry sample was identified as composed of 68 components and there were 2 components that were suspected as oil fingerprints namely khusimene (4.44%) and nootkatone (2.02%)